Inhibition of SARS-CoV-2 Replication by Acidizing and RNA Lyase-Modified Carbon Nanotubes Combined with Photodynamic Thermal Effect - Jianshe Yang (Diagnostic and Treatment Advances in COVID-19 and SARS-CoV-2, 2023)
The first patient suffering from severe acute respiratory syndrome (SARS) was identified in December 2019 in Wuhan, China. Physicians and scientists consequently diagnosed and identified this case of SARS as COVID-19, which was caused by infection with SARS-CoV-2, a new coronavirus. To date, it has spread as a global pandemic, with more than 2.5 million confirmed patients and 175 thousand deaths. Unfortunately, we have yet to find a specific effective therapy; although, some maintenance therapies are known to improve symptoms, partially referencing the experiences from anti-SARS-CoV and the Middle East respiratory syndrome. In addition, many clinical trials are completed or ongoing. Accordingly, a new strategy for development of therapeutic drugs is urgently needed. Here, we propose to prepare a kind of carbon nanotube with functions to exert acidification for cytoplasmic and local cellular temperature-rising through photothermal conversion, according to the physical and chemical nature of carbon nanotubes having been well applied to facilitate such a response. Dexterously, we will put the above effects into practice to inhibit SARS-CoV-2 replication with respect to the biological nature of coronavirus.